The Role of the Forensic Accounting Expert in the Prevention of Combating Corruption and Economic Crime - Andreea Cristina Savu; Raluca Mihaela Mircea (Boharu); Cristina Gabriela Vasciuc (Săndulescu) (Ovidius University Annals: Economic Sciences Series, 2022)
Crime and the institutional management of crime has become a leading topic in research, practice and education. According to various studies, detection of crimes happens by accident almost every year. Systematic detection is obviously still lacking considerably. The effectiveness of the fight against money laundering depends to a large extent on the organization of the problem of the system of collection, processing and use of information in the sphere of monitoring activities, which are necessary for detection, prevention of financial crime. The purpose of this article is to highlight the need to expand the accountant's area of competence by combining accounting and forensic investigation techniques, which will be a prerequisite in discovering and combating tax fraud. The essence of financial investigations as a practical activity consists in the application of a complex of knowledge of applied economics for the identification and elimination of different types of crimes.